Corporate sustainability reporting practices in Turkey - Bozaykut Bük, Tuba (My University, 2020)
Companies have increasingly adopted and implemented corporate sustainability practices as ethical and responsible businessguidelines, environment management systems, social responsibility projects. The increase in corporate sustainability practicescreate an interest in sustainability reporting for external disclosure of corporate sustainability. The current study aims toanalyse the corporate sustainability reporting practices by analyzing business groups in Turkey. The findings indicate that only21% of the examined business groups have sustainability reports, and thereby, sustainability reporting is low among Turkishbusiness groups. On the other hand, the limited number of business groups that report their sustainability practices arefound out to be closely committed to the principles of UN Global Compact. The study concludes by suggesting that legal andstructural frameworks are needed for a more developed sustainability reporting practices in Turkey.

İşletmelerin etik ve sorumlu iş pratikleri, operasyonel yönetim sistemleri ve sosyal sorumluluk projeleri gibi sürdürülebilirlik faaliyetlerini her geçen gün daha fazla uyguladıkları görülmektedir. Kurumsal sürdürülebilirlik yaklaşımının uygulamalara yansıyan bir yönü de sürdürülebilirlik raporlamasıdır. Bu çalışma, Türkiye'deki işletme gruplarının sürdürülebilirlik raporlama uygulamalarını incelemeyi amaçlamaktadır. Bulgular, incelenen işletme gruplardan sadece %21’inin sürdürülebilirlik raporu yayınladığını ve sürdürülebilirlik raporlamasının Türkiye'deki işletme gruplarınca yaygın bir şekilde benimsenmediğini göstermektedir. Öte yandan, sürdürülebilirlik uygulamalarını raporlayan sınırlı sayıda işletme grubunun, BM Küresel İlkeler Sözleşmesi ilkelerini rehber aldıkları ve faaliyetlerini bu ilkeler çerçevesinde raporladıkları tespit edilmiştir. Bulgulara dayanarak çalışma, Türkiye'de sürdürülebilirlik raporlaması uygulamalarının gelişimi için yasal ve yapısal çerçevelerin oluşturulmasını önermektedir.
Türkiye’de sürdürülebilirlik raporlaması uygulamaları
Keywords: Corporate Sustainability Management; Corporate Sustainability Reporting; Business Groups; Kurumsal Sürdürülebilirlik Yönetimi; Sürdürülebilirlik Raporlaması; İşletme Grupları